The Interactive Effect of Agricultural Input and Research and Development on Agricultural Sector Expansion - Gisore, Naftaly Mose; Were, Lawrence Ouru (Asian Development Policy Review, 2017)
The paper investigated the interactive effect of agricultural capital and labour input and research and development on agricultural sector expansion in East African Community between the period 2000 and 2014. According to the endogenous growth theory, research and development leads to increase in the stock of knowledge which in turn has got spillover effects hence leads to economic growth. However, empirical studies on the interactive effect on the agricultural sector are minimal in the EAC hence the study sought to fill this gap. The objective of this study was to determine the interactive effect of agricultural capital, labour and agricultural research and development on agricultural sector growth. Using Levin-Lin-Chu panel unit test, some variables were stationary at level while others were stationary after first differencing. Most panel diagnostic test concluded autocorrelation, heteroscedasticity and cross dependence was absent. Random effects regression results showed that interaction of R&D and capital had a positive relationship with agricultural expansion. While the interaction of agricultural R&D expenditure and agricultural labour had a significant negative relationship. The study recommends that R&D to be allocated more funds, firms to train agricultural labourers on how new technologies are being used and also to allocate them duties and responsibilities that match their skills and that agricultural capital costs be subsidized.